Nonlinear wave modulation in thin viscoelastic tube filled with inviscid fluid - Che Ahmed, Normaisarah; Choy, Yaan Yee; Tay, Kim Gaik (2018)
In the present paper, the modulation of nonlinear wave in a thin viscoelastic tube filled with inviscid fluid is studied. We assumed that the arterial wall material is an incompressible, isotropic and thin viscoelastic tube and considered blood as approximate equations of an incompressible inviscid fluid. Applying the reductive perturbation method, the Nonlinear Schrӧdinger (NLS) type equation as the evolution equation is obtained for the modulation of nonlinear wave in such a medium.